2004
DOI: 10.1136/gut.2004.042481
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathy precedes type 1 diabetes in the BB rat

Abstract: Background and aims: There is increasing evidence implicating intestinal immune responses to dietary proteins in the pathogenesis of type 1 autoimmune diabetes (T1D). Here we investigated the association between intestinal pathology and dietary factors in T1D by examining the mucosal architecture in the BB rat model. Methods: BB control (BBc) and diabetes prone (BBdp) rats were fed either a diabetes retardant hydrolysed casein based diet or one of two cereal based diets that promote the development of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 52 publications
10
64
1
Order By: Relevance
“…The natural history of intestinal abnormalities associated with human type 1 diabetes looks similar to that observed in diabetes-prone BB rats, in which the increased intestinal permeability precedes hyperglycaemia and lymphocytic insulitis, indicating enteropathy as a very early pathogenetic event [1][2][3]. In human type 1 diabetes the genesis and significance of the increased intestinal permeability is unknown.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The natural history of intestinal abnormalities associated with human type 1 diabetes looks similar to that observed in diabetes-prone BB rats, in which the increased intestinal permeability precedes hyperglycaemia and lymphocytic insulitis, indicating enteropathy as a very early pathogenetic event [1][2][3]. In human type 1 diabetes the genesis and significance of the increased intestinal permeability is unknown.…”
Section: Discussionmentioning
confidence: 69%
“…In the bio-breeding (BB) rat, a model of spontaneous autoimmune diabetes, increased intestinal permeability, mucosal lymphocytic infiltration and morphological changes have been reported [1][2][3]. More recently, an enteropathy with similar characteristics has also been described in the non-obese diabetic mouse [4].…”
Section: Introductionmentioning
confidence: 98%
“…We show that prediabetic NOD mice develop an intrinsic 'leaky' gut. This finding has been well characterised in the BioBreeding rat model of type 1 diabetes [3,5,6]. Watts et al [7] have suggested that intrinsic gut leakiness in BioBreeding rats may be caused by an increase in endogenous zonulin, a protein involved in modulating intestinal tight junctions.…”
Section: Discussionmentioning
confidence: 72%
“…Disruption of this delicate barrier promotes the initiation and development of intestinal autoimmune diseases such as coeliac disease [1] and inflammatory bowel disease [2]. Impaired intestinal barrier function has also been detected in rodent models of type 1 diabetes [3][4][5][6][7] and in type 1 diabetes patients and their relatives [8][9][10][11][12]. Changes in the intestine, induced by dietary or enteric antigens, have been proposed as causative factors in the course of type 1 diabetes [13,14]; however, the role of the gut and enteric microbes in type 1 diabetes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently identified a wheat storage globulin-like protein as a candidate diabetes-related antigen in diabetic rats and human patients [4]. There is evidence that the gut is mildly inflamed and abnormally permeable to lumen antigens in BBdp rats [10][11][12][13][14] and in human patients with type 1 diabetes [15][16][17][18]. However, remarkably little is known about the immune state of the gut-associated lymphoid tissue (GALT) in animals or humans that spontaneously develop type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%